Cognitive didactic in sports teaching game, perceptive aspects and desicionales (Revista horizonte, 2021)
The purpose of this study is to design and apply a didactic proposal to teach sports game, based on the inclusion of perceptual and decisional aspects of the players, translated into sequences of individual tactical actions, in the defense and attack dimensions of the sports game. The methodology used, considers two stages: first an exposition and sanction of the tactical-individual sequences to a judgment of experts. The second stage considered the experimental application of the sequences sanctioned in the previous stage, to a sample of athletes considered athletic talent in the stage of formation (13-16 years) ladies and men, belonging to the disciplines of Soccer, Handball and Hockey-roller skate. The results obtained show an increase of those game actions translated into an improvement of the game (anticipation, deterrence, efficient marking, efficient pass) in the attack as well as in defense, as well as a decrease in those actions of lower quality in the game (single pass, single dial).